Ray-tracing implicit functions - Stephani Puspita Kurniawan (2014)
The Persistence of Vision Raytracer (POV-Ray) is an open source ray tracer program that is widely used to render an image based on certain source code. One feature that makes POV-Ray outperform other ray tracers is that the images it rendered are high in quality and photo-realistic. Currently, POV-Ray is able to render images defined in wide variety of functions defined in its source code, including a single line user defined implicit function.